2019
DOI: 10.3389/fped.2019.00055
|View full text |Cite
|
Sign up to set email alerts
|

Two Unique Cases of X-linked SCID: A Diagnostic Challenge in the Era of Newborn Screening

Abstract: In the era of newborn screening (NBS) for severe combined immunodeficiency (SCID) and the possibility of gene therapy (GT), it is important to link SCID phenotype to the underlying genetic disease. In western countries, X-linked interleukin 2 receptor gamma chain (IL2RG) and adenosine deaminase (ADA) deficiency SCID are two of the most common types of SCID and can be treated by GT. As a challenge, both IL2RG and ADA genes are highly polymorphic and a gene–based dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This might explain the low lymphocyte count in our patient. Several reports confirmed that the mutations in IL2RG gene lead to X-SCID, an immunodeficiency disease, characterized by low lymphocyte counts [4,10,11]. Some studies reported that immunodeficiency might be one of the risk factors related to HPS [12,13].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This might explain the low lymphocyte count in our patient. Several reports confirmed that the mutations in IL2RG gene lead to X-SCID, an immunodeficiency disease, characterized by low lymphocyte counts [4,10,11]. Some studies reported that immunodeficiency might be one of the risk factors related to HPS [12,13].…”
Section: Discussionmentioning
confidence: 90%
“…However, HPS induced by Mycobacterium tuberculosis complex infection is extremely rare, and HPS related to M. bovis in children is not yet reported [ 2 , 3 ]. X-linked severe combined immunodeficiency (X-SCID) is also a rare, life-threatening immunodeficiency disease caused by genes mutations [ 4 ]. Thus, an extremely rare case of patient with X-SCID also presenting HPS due to M. bovis has been reported in this study.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the reliability of flow cytometry-based functional assays (e.g., measure of WASP protein, analysis of gamma chain signaling, assessment of superoxide production), together with the results of XCI studies in the mother, can allow making a diagnosis guiding more complex genomic analyses, for example to search for gene inversions, promoter mutations, and other rare genomic changes. The possibility of false negative exome-sequencing results was reported for WAS [ 10 ], X-SCID [ 95 ], and chronic granulomatous disease (CGD) [ 96 ]. Conversely, for some PIDs, also flow cytometry can yield false negative results, as reported about the expression of SAP protein in XLP [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the presence of maternal T-cells or leaky production of oligoclonal cells, total T-cell numbers might initially be significant, so the analysis of subpopulations including naïve T-cells and recent thymic emigrants (RTE) is crucial (23,25). The final diagnosis of SCID-X1 is established by the identification of pathogenic variants in the IL2RG gene, although sometimes this requires confirmation by other studies, such as functional assays, especially in atypical SCID-X1 (26). The expression of gc is not conclusive, as it can be normal (but nonfunctional) in some patients (10).…”
Section: Physiopathology Of Scid-x1mentioning
confidence: 99%